Kinematics of marathon running tactics part one: course profile - Erdmann, W. S.; Lipinska, P. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The paper presents a description of geometry of marathon courses. The following courses were taken into account: Edmonton 2001 (IAAF World Championships), Boston 2002 (city marathon), Berlin 2002 (city marathon), Athens 2004 (Olympic Games). Based on course profile (for every 1 km) coefficient of course difficulty was calculated. The most flat course profile was that of Berlin Marathon, the toughest profile was that of Athens Marathon.